Health, economic growth, and Gini index in North America using a panel model - Molina-Salazar, Raúl Enrique; Carbajal De Nova, Carolina (Horizonte Sanitario, 2023)
Objective: The objective of this paper is assessed the nexus among health status, economic growth, and the Gini index in North America and its countries using a panel model.Materials and Method: The materials consist of annual data regarding life expectancy, government health expenditure as percentage of the gross domestic product, Gini index, and gross domestic product at constant 2015 US$ for the period 2000-2019. The method applies a panel model for North America and its three countries: Canada, Mexico and The United States. North America diversity treatment among countries is dealt with fixed and random effects.Results: North America inhabitants health status are negatively influenced by an increasing income inequality, and a reduction on economic growth. The country that expends more in health care is The United States, follow by Canada and Mexico. The biggest reduction on life expectancy from an increase in income inequality is in The United States, followed by Canada and Mexico. Life expectancy increases when Canada and The United States experience economic growth. The countries with inarticulate health policy responses to an increase in income inequality are first Mexico followed by The United States.Conclusions: In North America and its countries an increasing income inequality reduces life expectancy, and government health expenditure. Economic growth benefits life expectancy and government health expenditure. Health status seems to improve with a reduction in income inequality and a greater public health expenditure. Therefore, policies that increases income inequality and reduces public health expenditure seems to be advocates of a reduction: in health status, population welfare and economic growth.